Effect of Fungal Enzymes on Decolorization of Textile Dyeing Industry Effluent - R., LATHIKA (Asian Journal of Biological and Life Sciences, 2017)
Enzyme technology has been receiving increased attention in the latest development of biological remediation. The present study is aimed to explore the potential of the fungal species to decolorize the dyes from textile dyeing industry effluent.The white rot fungi Phanerochaete chrysosporium and Ganoderma lucidum were cultured in the selected substrates like wheat bran and sugarcane bagasse. The fungal enzymes were extracted and purified. The raw effluent (undiluted) and the diluted effluent (25%, 50% and 75% dilution with MSM) were taken for the study. Both diluted and undiluted effluent were adjusted to varying pH ranging from 2.0 to 8.0 and inoculated with Phanerochaete chrysosporium and Ganoderma lucidum under controlled conditions and kept at room temperature for observation. Appropriate amount of the precipitated enzymes were added and kept in shaker for incubation at room temperature. Percentage decolorization was noted every 24 hours upto 7 days and calculated. From the results it was noted that the decolorization by the fungal species occurred effectively in 50% and 25% diluted effluent at pH 8.0. Whereas enzymatic decolorization occurred effectively in 75% diluted effluent at pH 5.0. It was noted that Phanerochaete chrysosporium and Ganoderma lucidum could decolorize up to 90.6% and 85.7% of textile dyeing industry effluent respectively. Whereas, the enzymes extracted from Phanerochaete chrysosporium and Ganoderma lucidum could decolorize up to 90.8% and 88.8% respectively. Hence, both the organisms can be exploited for the decolorization of various dyes that are released from textile dyeing industry.
Keywords: Fungal enzymes (xylanase and laccase); MSM- Minimal Salt Medium; Phanerochaete chrysosporium and Ganoderma lucidum